1997
DOI: 10.1021/ja970574c
|View full text |Cite
|
Sign up to set email alerts
|

Density Functional Study on the Electronic Structures of Model Peroxidase Compounds I and II

Abstract: The electronic structures of [Fe(Por)(Im)O] 1+ and [Fe(Por)(Im)O] (model compounds I and II, respectively) have been studied on the basis of density functional theory or DFT (Por ) porphine, Im ) imidazole). The a 2u π-cation radical state ( 4 A 2u ) was determined to be the ground state of compound I with total spin equal to 3 / 2 , while the a 1u π-cation state ( 4 A 1u ) was found to be 0.15 eV higher in energy than the 4 A 2u state. Since, in both states, the spins were localized to the porphyrin ring (S )… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
90
1
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(102 citation statements)
references
References 83 publications
10
90
1
1
Order By: Relevance
“…[16] Further computational studies showed that the degeneracy of the oxidant states also has consequences for substrate-activation mechanisms, which tend to lead to two-state reactivity (TSR) patterns with different rate constants and reaction mechanisms on both spin-state surfaces. [17] This TSR profile can result in the masquerade of kinetic isotope effects and the seemingly observance of multiple oxidants in the reaction mixture.…”
mentioning
confidence: 99%
“…[16] Further computational studies showed that the degeneracy of the oxidant states also has consequences for substrate-activation mechanisms, which tend to lead to two-state reactivity (TSR) patterns with different rate constants and reaction mechanisms on both spin-state surfaces. [17] This TSR profile can result in the masquerade of kinetic isotope effects and the seemingly observance of multiple oxidants in the reaction mixture.…”
mentioning
confidence: 99%
“…This result clearly shows how the distortion of the cofactor, the modification of the first coordination sphere of the metal and the rearrangement of the structure of the receptor are intrinsically correlated and not individual phenomena. The energy of the transition state is 20.7, 9.8 and 18.6 kcal mol 21 , above the absolute minimum of the system, for low-, intermediate-and high-spin systems, respectively (figure 4). They are sufficiently large to discard the possibility that the atomic motions at room temperature naturally allow the transition from glutamate bound (6) to glutamate unbound configurations (5 and 5 0 ).…”
Section: Analysis Of the Fe(iii)(schiff Base) Ho Resting Statementioning
confidence: 99%
“…However, it is still interesting to note that, in most cases, this part of the system remains almost unaffected (Fe(II) cases) or even stabilized (Fe(III) cases) for Fe -O glu going from reactant to a few steps after the transition state. From then on, a destabilization of the system is observed, reaching up to ca 15 kcal mol 21 (electronic supplementary material, figure S4). Structural analysis showed us that the first part of the transition implies a slight relaxation of helix A while the glutamate is removed.…”
Section: Electronic Transition and Activation Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…Electron abstraction from the porphyrin a 2u orbital results in high unpaired p-orbital spin density at the meso-carbons, while abstraction from the a 1u orbital results in appreciable unpaired p-orbital spin density at the pyrrole b-carbons. In general, alkyl or aryl substituents at the meso positions destabilize the a 2u orbital, favoring oxidation of porphyrins to p-cation radicals with 2 [24] (a downfield-shift of the meso-H signal may be attributed to induced spin polarization at the meso-carbon [70,71]). …”
mentioning
confidence: 99%